2017
DOI: 10.4236/ajps.2017.810167
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity of Coffee Accessions in Rwanda and Its Implication for Coffee Breeding

Abstract: Genetic variation is important in breeding programs because it determines the amount of gain from selection. This study was conducted to determine the magnitude of genetic diversity in coffee (Coffea arabica L.) accessions for developing superior cultivars in Rwanda. Twenty-one coffee accessions established in 1990 in an un-replicated field experiment at the Rubona Experimental Station of the Rwanda Agriculture Board (RAB) located in the mid-altitude zone of Rwanda, were used in the study. Data were recorded o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…The finding of this study was in agreement with some research results [ 2 , 5 , [65] , [66] , [67] , [68] , [69] ] who reported that higher number of nodes were observed when coffee seedlings grown using organic amendments possibly due to the availability of rich organic carbon [ [15] , [16] , [17] , [18] , [19] ] that eventually improves growth media porosity, aeration, nutrient uptake and water retention capacity (Adrinal et al, 2021).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The finding of this study was in agreement with some research results [ 2 , 5 , [65] , [66] , [67] , [68] , [69] ] who reported that higher number of nodes were observed when coffee seedlings grown using organic amendments possibly due to the availability of rich organic carbon [ [15] , [16] , [17] , [18] , [19] ] that eventually improves growth media porosity, aeration, nutrient uptake and water retention capacity (Adrinal et al, 2021).…”
Section: Resultssupporting
confidence: 94%
“…The current findings concur with Teixeira et al [ 65 ], Muvunyi et al [ 66 ], Rodrigues et al [ 67 ] and Netsere and Kufa [ 69 ] who reported that internode lengths of coffee seedlings significantly varied in different plant growth media compositions, probably due to the fertility variation of the organic amendment [ 68 ] and the variation in growing condition [ 64 ]. Besides, DaMatta et al [ 71 ] and Ribeirinho et al [ 50 ] supported that the internode length of coffee seedlings in soil with enough organic matter is longer compared with seedlings grown merely in topsoil.…”
Section: Resultssupporting
confidence: 91%
“…Unique genes can only come from these divergent cluster families. The existence of both very divergent and uniform genotypes among coffee germplasm was also observed by Muvunyi et al (2017).…”
Section: Discussionmentioning
confidence: 83%
“…In Rwanda, the majority of the agricultural produce is Dusengemungu et al 69 food crops instead of export crops which results in generating low incomes for the farmers (Muvunyi et al, 2017). Primarily due to numerous challenges that result in low crop production including shortage of arable land and mismanagement of available land, inadequate rainfall (climate uncertainties), soil infertility, pest and disease control, limited technology base, to cite a few.…”
Section: Challenges Of Agriculture In Rwandamentioning
confidence: 99%
“…The practice now is targeting the small-scale farmers and it is hoped to increase productivity, therefore, contributing to the food security and poverty eradication. Choosing the right high productive and reliable breed of cultivated plants is very recommended and should be more exploited by all sectors involved in agriculture (Musoni, 2016;Muvunyi et al, 2017).…”
Section: Modern Agriculture and Plant Biotechnology Status In Rwandamentioning
confidence: 99%